2022
DOI: 10.1002/adhm.202201349
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitive and Conductive Hydrogel Induced Innerved Bone Regeneration for Infected Bone Defect Repair

Abstract: Repairing infected bone defects is a challenge in the field of orthopedics because of the limited self-healing capacity of bone tissue and the susceptibility of refractory materials to bacterial activity. Innervation is the initiating factor for bone regeneration and plays a key regulatory role in subsequent vascularization, ossification, and mineralization processes. Infection leads to necrosis of local nerve fibers, impeding the repair of infected bone defects. Herein, a biomaterial that can induce skeletal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 48 publications
(57 reference statements)
0
25
0
Order By: Relevance
“…Innervation is an important initiator of bone regeneration and is involved in the process of bone growth and repair, so the importance of nerve regeneration needs to be taken into account when using tissue-engineered scaffolds to repair bone defects. In this way, Jing et al 58 used magnesium-modified black phosphorus (BP@Mg) incorporated into GelMA to prepare a photosensitive conductive hydrogel for infected bone defects and found that it not only had efficient antibacterial properties, but also promoted nerve and bone growth. Vascularised osteogenesis is essential for successful bone regeneration, so promoting vascular growth while treating bone defects is an important strategy.…”
Section: Application Of Gelma Hydrogel In Musculoskeletal Diseases Ge...mentioning
confidence: 99%
“…Innervation is an important initiator of bone regeneration and is involved in the process of bone growth and repair, so the importance of nerve regeneration needs to be taken into account when using tissue-engineered scaffolds to repair bone defects. In this way, Jing et al 58 used magnesium-modified black phosphorus (BP@Mg) incorporated into GelMA to prepare a photosensitive conductive hydrogel for infected bone defects and found that it not only had efficient antibacterial properties, but also promoted nerve and bone growth. Vascularised osteogenesis is essential for successful bone regeneration, so promoting vascular growth while treating bone defects is an important strategy.…”
Section: Application Of Gelma Hydrogel In Musculoskeletal Diseases Ge...mentioning
confidence: 99%
“…Postoperative infection is a key cause of bone repair failure in the clinical application of bone implants, which makes orthopedic surgeons face the challenge of formulating local antibiotic treatment strategies to prevent infection and promote bone healing. , As an emerging treatment modality, near-infrared (NIR) light-assisted hyperthermia has made amazing progress in tumor ablation and antibacterial therapy. , However, excessive temperature can cause damage to normal tissue at the lesion, so it is necessary to explore NIR light-triggered antibacterial synergistic therapy within a safe temperature range. Phase-change materials (PCM) are simple and effective controlled-release platforms due to their accurate response to temperature. , When the temperature reaches the melting point of the PCM to trigger the solid-to-liquid phase transition, the payloads can be released with the flow .…”
Section: Introductionmentioning
confidence: 99%
“…In one study, the gelatin methacryloyl (GelMA) was combined with magnesium-modified black phosphorus nanosheets (BP@Mg) to fabricate a photosensitive conductive GelMA-BP@Mg (GBM) hydrogel for healing infected bone (Fig. 5 b) [ 90 ]. When exposed to NIR light, the GBM hydrogel displayed effective antibacterial effects and decreased the inflammation caused by infection because of the photothermal properties of the BP@Mg.…”
Section: Nanomaterials and Hydrogels For Biohybrid Hybrogelsmentioning
confidence: 99%
“…5 a Schematic diagram of a visible-light-mediated nano-biomineralization method for the synthesis of BTH through the photocatalytic activity of ruthenium. Reproduced with permission from [ 88 ], copyright American Chemical Society, 2022. b Schematic images of the fabrication process of GelMA-BP@Mg composed of GelMA and BP@Mg and exhibiting the photothermal properties of the GelMA-BP@Mg. Reproduced with permission from [ 90 ], copyright John Wiley and Sons, 2021. c Schematic images of the fabrication process of ECM-Au NP-based composite hydrogel and encapsulation of cardiac cells for heart disease (ischemia–reperfusion) treatment. Reproduced with permission from [ 94 ], copyright John Wiley and Sons, 2021 …”
Section: Nanomaterials and Hydrogels For Biohybrid Hybrogelsmentioning
confidence: 99%